2015
DOI: 10.1007/s10880-015-9425-8
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perception and Well-Being Among Persons with Multiple Sclerosis and Their Caregivers

Abstract: This study jointly examined illness beliefs held by persons with multiple sclerosis (PwMS) and caregivers in relation to well-being. A group of 68 PwMS and their caregivers completed the Revised Illness Perception Questionnaire, Psychological Well-being Scales, Satisfaction with Life Scale and Positive Affect and Negative Affect Schedule. Findings revealed that PwMS' well-being was primarily predicted by their own illness beliefs, and that also caregivers' well-being was primarily predicted by their own belief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 50 publications
8
52
1
Order By: Relevance
“…The role of EWB appears to be crucial also for the adaptation to neurological conditions, such as MS. Strober () found that the levels of flourishing in MS patients were influenced by the presence of a Type D personality diagnosis, by the levels of depression and by the disease management skills. Similarly, Bassi et al () documented that EWB (measured with Ryff's PWB) was negatively associated with negative emotional response to the illness in MS patients. Moreover, authors found that PWB was higher in those patients who reported a better understanding of their illness.…”
Section: Discussionmentioning
confidence: 88%
“…The role of EWB appears to be crucial also for the adaptation to neurological conditions, such as MS. Strober () found that the levels of flourishing in MS patients were influenced by the presence of a Type D personality diagnosis, by the levels of depression and by the disease management skills. Similarly, Bassi et al () documented that EWB (measured with Ryff's PWB) was negatively associated with negative emotional response to the illness in MS patients. Moreover, authors found that PWB was higher in those patients who reported a better understanding of their illness.…”
Section: Discussionmentioning
confidence: 88%
“…In this model, people regulate both their behavioral and emotional reactions to illness based on 1) ideas about the label and nature of illness and its associated symptoms and the targets for change (identity); 2) beliefs about why they developed their illness (causes), 3) perceptions regarding amenability of the illness to being cured, prevented, or treated (cure/control); 4) beliefs about the seriousness of the disease and impact upon the everyday individuals’ life (consequences); 5) beliefs about how long an illness may last, including symptoms and recovery (timeline‐acute/chronic); 6) feelings that arise as a result of the illness, such as anxiety or depression following diagnosis of a condition (emotional representations); 7) degree to which individuals feel they understand a specific illness (illness coherence); and 8) perceptions about variability in symptoms (timeline‐cyclical) . Strong illness identity, high emotional representations, low illness coherence, low personal control, low treatment control, severe perceived consequences, and chronic perceived timeline of illness have been shown to be related to poor well‐being, higher psychological distress, and slower recovery in various chronic illnesses …”
Section: Introductionmentioning
confidence: 99%
“…In this multivariable logistic model, older age at immigration is Although limited data exist in MS, recent research suggests that MS-related well-being is primarily predicted by patients' own illness beliefs. Bassi and colleagues 17 also showed that beyond the beliefs of the individuals affected with MS, the caregivers' well-being was primarily predicted by their own beliefs as well. General self-efficacy, perception of treatment control, and realistic MS timeline perspectives have been reported to be important correlates of self-management in MS, more so than clinical variables.…”
Section: The Risk Of Strong Emotions In Hispanic Immigrantsmentioning
confidence: 98%
“…15 Recently, illness perceptions have been described in white populations to be important determinants of MS treatment preference and management. [16][17][18][19][20] However, perceptions of the cause of MS have not been particularly studied in Hispanic Americans with MS. Understanding perceptions of illness in Hispanics with MS could nurture the development of culturally competent programs, identify gaps in health-care efficacy, and provide an avenue for future health interventions to reduce ethnic and racial disparities in MS.…”
Section: Study Populationmentioning
confidence: 99%